99 ASSESSMENT AND MANAGEMENT OF PAIN IN OLDER ADULTS WITH ACUTE FRACTURE ADMITTED UNDER AN ORTHOPAEDIC SERVICE. (18th November 2021) - Killeen, E; Doyle, K; O'Toole, R; Doran, T; Collins, D; Brewer, L
Abstract: Background: Older adults with acute fractures often have suboptimal pain control, in particular those with cognitive impairment. Effective pain management improves rehabilitation engagement and earlier discharge from acute care. Our study aimed to evaluate pain management of older adults with acute fracture admitted under an orthopaedic service in a tertiary hospital. Methods: Prospective review of patients over 65 years with an acute fracture admitted under an orthopaedic service. Review of chart, medication prescription and pain status. Data included type of fracture, comorbidities, cognitive status and analgesia prescribed. Data analysed using Excel. Results: 40 inpatients included. Median age 82 years (range 65-93 years), 70% female. 53% had cognitive impairment, ranging from mild to severe dementia. 75% had >5 regular medications pre-admission. 80% had >5 comorbidities. Two-thirds (73%) had an acute hip fracture. Most (80%) inpatients had a surgical intervention, the remaining were managed conservatively. Analgesia prescriptions included paracetamol for almost all patients (95%), non-steroidal anti-inflammatory drugs for 3 (8%) and regular opioids in only 3 (8%). 43% of patients reported pain at time of data collection. 13% had analgesia changed in the 24 hours beforehand. Pain adversely affected function in 205 and mobility in 28%. 2 patients were unable to verbalise pain however no pain scales or visual assessments were used. Documentation of pain assessment was best by nurses (100%) followed by doctors (60%) and allied health professionals (40%). Conclusion: Older adults with acute fracture are often multimorbid with cognitive impairment. This patient population are often untreated for pain with suboptimal pain assessment and analgesia review or prescriptions. Consequently we developed a pain policy for use on our orthopaedic service as a guide for effective pain assessment and management for older adults with acute fracture.